Prior histories of posttraumatic stress disorder and major depression and their onset and course in the three months after a motor vehicle collision in the AURORA study. Issue 1 (15th November 2021) - Joormann, Jutta; Ziobrowski, Hannah N.; King, Andrew J.; Gildea, Sarah M.; Lee, Sue; Sampson, Nancy A.; House, Stacey L.; Beaudoin, Francesca L.; An, Xinming; Stevens, Jennifer S.; Zeng, Donglin; Neylan, Thomas C.; et al.
Abstract: Background: A better understanding of the extent to which prior occurrences of posttraumatic stress disorder (PTSD) and major depressive episode (MDE) predict psychopathological reactions to subsequent traumas might be useful in targeting posttraumatic preventive interventions. Methods: Data come from 1306 patients presenting to 29 U.S. emergency departments (EDs) after a motor vehicle collision (MVC) in the advancing understanding of recovery after trauma study. Patients completed self‐reports in the ED and 2‐weeks, 8‐weeks, and 3‐months post‐MVC. Associations of pre‐MVC probable PTSD and probable MDE histories with subsequent 3‐months post‐MVC probable PTSD and probable MDE were examined along with mediation through intervening peritraumatic, 2‐, and 8‐week disorders. Results: 27.6% of patients had 3‐month post‐MVC probable PTSD and/or MDE. Pre‐MVC lifetime histories of these disorders were not only significant (relative risk = 2.6–7.4) but were dominant (63.1% population attributable risk proportion [PARP]) predictors of this 3‐month outcome, with 46.6% prevalence of the outcome among patients with pre‐MVC disorder histories versus 9.9% among those without such histories. The associations of pre‐MVC lifetime disorders with the 3‐month outcome were mediated largely by 2‐ and 8‐week probable PTSD and MDE (PARP decreasing to 22.8% with controls for these intervening disorders). Decomposition showed that pre‐MVC lifetime histories predicted both onset and persistence of these intervening disorders as well as the higher conditional prevalence of the 3‐month outcome in the presence of these intervening disorders. Conclusions: Assessments of pre‐MVC PTSD and MDE histories and follow‐ups at 2 and 8 weeks could help target early interventions for psychopathological reactions to MVCs.